The impact of surface projection on military tactics comprehension. Issue 1 (2nd January 2019) - Boyce, Michael W.; Rowan, Charles P.; Shorter, Paul L.; Moss, Jason D.; Amburn, Charles R.; Garneau, Christopher J.; Sottilare, Robert A.
ABSTRACT: This experiment assessed how displaying information onto different surfaces (flat vs. raised) influenced the performance, workload, and engagement of cadets answering questions on military tactics. Sixty-two cadets in a within-subjects design each answered 24 tactics-related questions across 2 conditions (12 on flat, 12 on raised) which were measured by accuracy and time on task. After each set of 12 questions, the cadets took postsurveys assessing engagement, measured by a modified User Engagement Scale and the System Usability Scale, and workload measured by the NASA-TLX. Findings indicated that raised terrain surface led to reduced workload and increased engagement and time on task as compared to the flat terrain surface. A practice effect drove performance metrics (time on task and accuracy), where the learner performed better on the second surface type displayed. This research contributes to expanding the literature base that supports alternative display methods to increase engagement and augment instruction of military tactics tasks.